Synergistic Effects of Lambda cyhalothrin Incorporated into 1, 4-dichlorobenzene for the Control of sand fly and mosquito vectors in Baringo and Kirinyaga Counties, Kenya - Josyline, Kaburi; Philip, Ngumbi; Lucy, Irungu; Paul, Ndegwa; Johnstone, Ingonga; Osero, Bernard; Libendi, Dickson; Christopher, Anjili (Asian Journal of Biological and Life Sciences, 2018)
Current efforts at mosquito control of malaria rely heavily on insecticide-treated bed nets, indoor residual spraying with insecticide, and application of chemical larvicides. No new public health insecticides have been developed for mainstream vector control in disease endemic countries for 30 years. Marigat study site is an area that is endemic for both cutaneous and visceral leishmaniasis while Mwea is a malaria endemic area. Both sand fly and mosquito collections were carried out in the study households before and after interventions using the CDC light traps. For laboratory bioassays, mosquitoes and sand flies were exposed to a dosage of 100 mg/m2 and their repellency and mortality monitored and scored over a period of 48 hours. For the field studies, vector collections were carried out before and after interventions. They were then counted identified and recorded. Results revealed high mortality rates of vectors exposed to the combination of PCB and ICON as compared to individual treatment of the two. The sand fly and mosquito densities decreased significantly when exposed to PCB/ICON combination as opposed to ICON and PCB alone. The mean numbers of sand flies and mosquitoes collected from houses with PCB/ICON combination was less as compared to PCB and ICON independently. From the results, there was a synergistic effect observed when lambda-cyhalothrin (ICON®) and 1, 4-dichlorobenzene (PCB®) are used in combination as compared to their individual treatments. This indicates that combinations are more effective in controlling vectors of malaria and leishmaniases diseases.
Keywords: Lamdacyhalothrin; Leishmaniasis; Malaria; Para-Dichlorobenzene